Potentiation of beta-lactam antibiotics against Mycobacterium tuberculosis by 2-aminoimidazoles: investigation into the mechanism of action and its relevance to mycobacterial bioenergetics - Jeon, Albert Byungyun, author; Basaraba, Randall J., advisor; Borlee, Brad, committee member; Gustafson, Daniel, committee member; Jackson, Mary, committee member; Melander, Christian, committee member; Obregón-Henao, Andrés, committee member (Colorado State University. Libraries, 2017)
Tuberculosis, caused by Mycobacterium (M.) tuberculosis, is a global health problem still causing morbidity and mortality due in part to the emergence of drug-resistance and the lack of new antimicrobial agents to treat the disease. While infection with drug-sensitive M. tuberculosis has cure rates between 90-95% with the conventional multidrug-regimen comprised of four different first-line anti-tuberculosis drugs, administered for a minimum of 6 months. In the event where premature termination of the treatment or poor patient compliance occurs, the disease may progress into latent tuberculosis, which holds the risk of reoccurring disease or even leads to development of drug-resistant strains that are refractory to first line anti-tuberculosis drugs. This persistence is a major hurdle in global tuberculosis control and warrants the development of a new class of anti-tuberculosis drugs or novel strategies to target persisting bacilli. However, the current anti-tuberculosis drug pipeline does not suggest an immediate solution required for the successful control of global tuberculosis epidemic. In sum, there is an urgent need for a new strategy to complement current tuberculosis chemotherapy. 2-aminoimidazoles and their derivatives have been shown to be effective inhibitors of bacterial biofilms. Not only does this class of small molecules inhibit the formation of or disperse biofilms, but they also exhibit a clinically relevant feature of potentially abrogating antibiotic resistance in important pathogenic bacteria. From the studies characterizing persistent M. tuberculosis bacilli after anti-tuberculosis therapy in animal models, it has been suggested that this subpopulation of bacilli share similarities with bacterial biofilms. Our group developed an in vitro culture system where M. tuberculosis can be cultured in biofilm-like surface-attached communities with host-derived macromolecules and showed they express extensive drug-tolerance to one of the first-line anti-tuberculosis drug, isoniazid. Based on the previous effects of 2-aminoimidazoles on biofilms and drug-resistant bacteria, we hypothesized that 2-aminoimidazoles could reverse phenotypic drug-tolerance expressed by M. tuberculosis in our model and demonstrated that, indeed, derivatives of 2-aminoimidazoles effectively resensitized drug-tolerant bacilli to isoniazid. Additionally, a fortuitous but critical observation was made in which one of the potent 2-aminoimidazole derivatives potentiated the effect of ß-lactam antibiotics against M. tuberculosis. As repurposing ß-lactams in tuberculosis treatment regimen has potential therapeutic value, which are described throughout this dissertation. In chapter 2, 2-aminoimidazole compounds are shown to be effective at potentiating multiple ß-lactam antibiotics. Minimum inhibitory concentrations, as well as bactericidal concentrations, of ß-lactams were dramatically reduced when combined with 2-aminoimidazoles. Through a transcriptional analysis of M. tuberculosis treated with 2B8, one of our lead 2-aminoimidazoles induced cell envelope related stress responses and suppressed mycolic acid biosynthesis. Thereafter, it was hypothesized that 2-aminoimidazoles disrupts one or more factors conferring M. tuberculosis ß-lactam resistance, which we shown in chapter 3 is in large part due to a reduction in secretion of the enzyme ß-lactamase and by increasing cell envelope permeability. 2B8 treated M. tuberculosis exhibited significantly lower ß-lactamase activity in culture supernatant, which was due to a general protein secretion defect, and not from direct inhibition of ß-lactamase enzyme activity by 2-aminoimidazole compounds. As expected from the transcriptional analysis, 2B8 induced alterations in cell envelope lipid composition highlighted by the accumulation of trehalose monomycolate, the reduction of trehalose dimycolate, as well as a decrease in mycolic acid biosynthesis. Additionally, increased sensitivity to the detergent SDS, increased permeability to multiple nucleic acid staining dyes, and increased bindings of peptidoglycan-targeting antibiotics were observed when with 2B8 treatment. Based on major findings from chapter 3, it was hypothesized that the underlying mechanisms of 2-aminoimidazoles are the disruption of proton motive force and the disturbance of mycobacterial bioenergetics. In chapter 4, the collapse of proton motive force with additional dose-dependent block of mycobacterial electron transport chain is highlighted. Through a series of assays, we determined that 2B8 blocks the M. tuberculosis electron transport chain downstream of complex I and II, but upstream of complex IV. Taken together, these results collectively extend our current understanding of the various effects 2-aminoimidazole treatment has on M. tuberculosis susceptibility to ß-lactam antibiotics through perturbation of mycobacterial bioenergetics which can provide a profound impact in improving current tuberculosis therapy. Furthermore, this study offers valuable information for the construction of the next generation of potent 2-aminoimidazoles to improve efficacy against M. tuberculosis as well as other compounds that may be developed as a new anti-TB drug targeting bioenergetics.
Keywords: beta-lactam; bioenergetics; beta-lactamase; 2-aminoimidazoles; cell envelope; Mycobacterium tuberculosis